Three-dimensional visualization of magnetic domain structure with strong uniaxial anisotropy via scanning hard X-ray microtomography - Suzuki, Motohiro; Kim, Kab-Jin; Kim, Sanghoon; Yoshikawa, Hiroki; Tono, Takayuki; Yamada, Kihiro T.; Taniguchi, Takuya; Mizuno, Hayato; Oda, Kent; Ishibashi, Mio; Hirata, Yuushou; Li, Tian; et al. (Applied physics express, 2018)
An X-ray tomographic technique was developed to investigate the internal magnetic domain structure in a micrometer-sized ferromagnetic sample. The technique is based on a scanning hard X-ray nanoprobe using X-ray magnetic circular dichroism (XMCD). From transmission XMCD images at the Gd L3 edge as a function of the sample rotation angle, the three-dimensional (3D) distribution of a single component of the magnetic vector in a GdFeCo microdisc was reconstructed with a spatial resolution of 360 nm, using a modified algebraic reconstruction algorithm. The method is applicable to practical magnetic materials and can be extended to 3D visualization of the magnetic domain formation process under external magnetic fields.